Raja Mahendra Pratap: A Visionary Leader for Modern India - rana , Rakesh (Innovative Research Thoughts, 2018)
Raja Mahendra Pratap was a brilliant and forward-thinking ruler who had a major impact on India's fight for independence and subsequent progress. A prince from the Uttar Pradesh state of Mursan, he was born in 1886. But he wasn't satisfied with luxury and instead devoted himself to the betterment of his country. He was inspired by Mahatma Gandhi and shared his belief that liberation could be won without resorting to violence against the British. During World War I, he played a pivotal role by helping the German government set up a provisional government in Afghanistan on behalf of the Indian subcontinent. The government's goals included gaining worldwide recognition for India as a sovereign country and rallying support for India's independence. The efforts of Raja Mahendra Pratap in this respect were crucial in bringing international attention to India's fight for independence. Education and social transformation were two of Raja Mahendra Pratap's primary concerns. Education and empowering underprivileged groups, in his view, were crucial to the nation's development. He dedicated his life to improving access to higher education for low-income residents of his home area. The courage and foresight of Raja Mahendra Pratap, who led India to freedom, remain to be an inspiration to Indians today. His life and work are a testament to the value of hard work, education, and social change in creating a more prosperous and advanced India. His efforts to the liberation fight and nation-building made him a respected figure in Indian history, and his vision for an unified and wealthy India remains relevant even today.